Essays in economics - McGuinness, Anne (Trinity College (Dublin, Ireland). Department of Economics, 2011)
This Ph.D thesis examines the following societal issues: the shortfall in Irish pension funding, households' decisions to provide for retirement, households' decision to own a home, and total factor productivity convergence through learning.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin.